KOMPETENSI PUSTAKAWAN DAN OPTIMALISASI TEKNOLOGI INFORMASI UNTUK MENINGKATKAN KUALITAS LAYANAN PEMUSTAKA DIFABEL - Heri Abi Burachman Hakim; Wiyarsih Wiyarsih (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
Every citizen is entitled to education is not the exception of persons with disabilities (disfabel). The existence of inclusive schools is a form of government attention to realize education for difabel.Perpustakaan as one of the important means for education should come to realize the library-based inclusion, the library is not only serve for non-disabled pemustaka but also for disabled pemustaka.Namun up to now there are many libraries capable and ready in providing services to disabled users, both in terms of infrastructure and human resources. This will undoubtedly hinder the learning process of people with disabilities who have limitations. For that library needs to provide facilities for infrastructure that facilitate difable pemustaka in utilizing library services especially facilities and infrastructure information technology.In addition, librarians are also required to have special competence both softskill and hardskill to serve difabel pemustaka so that disabled users feel the convenience and ease in utilizing the service library.